The Implementation of Compensation of Rights of Ownership on Land in the Development of Toll Road in Dumai City, Riau Province - Hutapea, Maria (Westscience Press, 2024)
This paper is based on the research in Dumai City in 2019. Frequently, in the implementation of land acquisition resettlement for general interest development emerged issue in compensation. The former land owner whose land has been used for development of toll road Pekanbaru – Dumai (in this matter is in Bagan Besar Urban Village, Dumai City) didn’t feel satisfied with the compensation they had received. In the Article 1 point 10 of the Law Number 2 of 2012 on Land Acquisition Resettlement for General Interest Development is regulated that Compensation is the adequate and fair compensation to the parties who has rights in the process of Land Acquisition Resettlement. This research is empirical legal research. The result of this research shows that principle of adequate and fair has not been implemented.